Transcatheter Closure of Ruptured Sinus of Valsalva Aneurysm: Early Experience from Nepal - Shrestha, Manish; Shah, Subash; Manadhar, Reeju; Yadav, Dharmanath; Kansakar, Subodh Bir Singh; Rajbhandari, Sujeeb; Aryal, Shilpa; Prajapati, Dipanker; Adhikari , Chandra Mani (Nepalese Heart Journal, 2026)
Background: Ruptured sinus of Valsalva aneurysm (RSOV) is a rare but potentially life-threatening condition traditionally managed with surgery. Transcatheter closure (TCC) has recently emerged as a less invasive alternative. Case Summary: We report two adult patients; a 27-year-old male and a 48-year-old female, with RSOV arising from the non-coronary sinus and rupturing into the right atrium. Both presented with palpitations and dyspnea. Multimodality imaging confirmed the diagnosis. TCC was successfully performed using a Cera duct occluder in the first case and a Cocoon duct occluder in the second. Post-procedure imaging showed optimal device position, preserved aortic valve function, and no significant residual shunt, with no procedural complications. Conclusion: Transcatheter closure of RSOV is a safe and effective alternative to surgery in selected patients.